2019
DOI: 10.1186/s41240-019-0129-0
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Vibrio species isolated from cultured olive flounder (Paralichthys olivaceus) in Jeju Island, South Korea

Abstract: Olive flounder (Paralichthys olivaceus) is the major species developed for aquaculture in South Korea. Over the long history of olive flounder aquaculture, complex and diverse diseases have been a major problem, negatively impacting industrial production. Vibriosis is a prolific disease which continuously damages olive flounder aquaculture. A bacterial disease survey was performed from January to June 2017 on 20 olive flounder farms on Jeju Island. A total of 1710 fish were sampled, and bacteria from the exter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 30 publications
3
14
0
Order By: Relevance
“…None of V. parahaemolyticus found in the samples. The same ndings were reported and identi ed that Vibrio species was isolated from cultured olive ounder (Paralichthys olivaceus) in Jeju Island, South Korea and that there was no presence of V. parahaemolyticus, too (Sohn, Kim, Jin, & Lee, 2019). This was also reported by Hoang Tan Quang et al (2020) in which V. parahaemolyticus strain was a pathogen causing shrimp diseases, (Dao, Linh, & Khanh, 2014), (Khanh et al, 2019).…”
Section: Discussionsupporting
confidence: 63%
“…None of V. parahaemolyticus found in the samples. The same ndings were reported and identi ed that Vibrio species was isolated from cultured olive ounder (Paralichthys olivaceus) in Jeju Island, South Korea and that there was no presence of V. parahaemolyticus, too (Sohn, Kim, Jin, & Lee, 2019). This was also reported by Hoang Tan Quang et al (2020) in which V. parahaemolyticus strain was a pathogen causing shrimp diseases, (Dao, Linh, & Khanh, 2014), (Khanh et al, 2019).…”
Section: Discussionsupporting
confidence: 63%
“…None of V. parahaemolyticus presence, the same reported of Sohn showed that identification of Vibrio species isolated from cultured olive flounder (Paralichthys olivaceus) in Jeju Island, South Korea that none of V. parahaemolyticus Fig. 4 Phylogenetic tree of 30 strain bacteria Vibrio varieties collected based on the 16S rRNA region by the UPGMA method presence too (Sohn, Kim, Jin, & Lee, 2019). In which V. parahaemolyticus strain was a pathogen causing in shrimp disease, (Dao, Linh, & Khanh, 2014), (Khanh et al, 2019).…”
Section: Discussionmentioning
confidence: 72%
“…The digestive system has the most common Vibrio species (V. alginolyticus, V. azureus and V. uvialis). None of V. parahaemolyticus presented, the same reported and identi ed that Vibrio species was isolated from cultured olive ounder (Paralichthys olivaceus) in Jeju Island, South Korea that none of V. parahaemolyticus presence too (Sohn, Kim, Jin, & Lee, 2019). In which V. parahaemolyticus strain was a pathogen causing in shrimp disease, (Dao, Linh, & Khanh, 2014), (Khanh et al, 2019).…”
Section: Discussionmentioning
confidence: 83%